Pengembangan Bahan Ajar Berbantuan Reading Box dalam Teks Cerpen Siswa Kelas XI SMA Swasta Al-Hikmah Medan - Sari, Maya; Safina, Nila; Soraya, Ratna (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to develop and assess the feasibility and effectiveness of teaching materials, specifically Reading Box-assisted materials, for short story texts in class XI SMA. The population comprised 194 students, with a sample of 48. The research utilized a research and development approach and the ADDIE development model, encompassing analysis, design, development, implementation, and assessment stages. The study yielded student books for learning and teaching, validated by design and material experts, Indonesian language teachers, and student responses. Validation results indicated an overall percentage of 86%, categorized as "Very Eligible." The effectiveness, assessed through student learning completeness, achieved an overall percentage of 85%. Consequently, the developed teaching materials prove both feasible and effective for implementing Indonesian language learning in class XI SMA, specifically focusing on short story texts.